Prevent postoperative urinary retention in day surgery adult patients: evidence-based quality improvement project. Issue 4 (14th December 2022) - Eddie, Cristie Subang; Norzan, Mohamad Norisham Bin; Mustafa, Anith Al Bakri; Ong, Shu Jie; Chan, Jiah Hui; Bation, Jeanibeth Molde; Owe, Sze Ling; Goh, Mien Li
ABSTRACT: Introduction and aims: Postoperative urinary retention (POUR) is a complication that often leads to adverse outcomes and prolonged hospital stay if treatment is delayed. The aim of this project was to improve the competence of nurses in the provision of preoperative POUR education and ensure all patients received preoperative POUR education, and hence reduce the incidence of POUR. Methods: The evidence-based quality improvement project utilized JBI's Practical Application of Clinical Evidence System and Getting Research into Practice module, adopting two POUR best practice recommendations and two audit criteria. The first criterion was for nurses to conduct preoperative education on POUR and the second criterion was to initiate early ambulation of postoperative patients. The project was implemented in three phases from June 2019 to August 2020 in short-stayer and day surgery wards. Results: Criteria 1 and 2 revealed low compliance of 0 and 30%, respectively, during preimplementation audit. There were significant improvements in the first and second cycles of postimplementation audit for both criteria 1 and 2. Our results indicated that most of the patients who were ambulated early were able to void urine. However, there were a few incidents of urinary retention reported despite early ambulation. Following the audit of the third cycle of postimplementation, the compliance for both criteria were found to be satisfactory (criteria 1: 87%, criteria 2: 82%). Conclusion: The implementation of the evidence-based quality improvement project reduced the incidence of POUR. A standardized management would enable nurses to provide consistency in care and effective management and hence prevent the occurrence of POUR.